Understanding drought tolerance of Bambara groundnut (Vigna subterranea (L.)Verdc.)in different agro-ecologies of Nigeria - Faloye, Benjamin Busuyi (2024)
Bambara groundnut (BG) (Vigna subterranea (L.) Verdc.) is a legume seed crop with high nutritional contents. It is a drought tolerant crop plant, and it is predominantly found in sub-Saharan Africa. Assessment of the available diversity using morphological and molecular approaches is an essential step to understand the genetics of complex traits including drought tolerance and to develop new high-yielding and climate-resilient varieties.